Early changes in peripheral blood cytokine levels after the treatment of metastatic hepatic carcinoma with CalliSpheres microspheres drug-eluting beads transcatheter arterial chemoembolization - Liu, Ying; Liu, Song; Zhao, Guang Sheng; Li, Xiang; Gao, Fei; Ren, Zhi Zhong; Bian, Jie; Wu, Jian Lin; Zhang, Yue Wei (Frontiers in Oncology, 2022)
Objective: To observe the early changes in peripheral blood cytokine levels after treatment of metastatic hepatic carcinoma (MHC) with CalliSpheres microspheres drug-eluting beads (DEB) transcatheter arterial chemoembolization (CSM-TACE). Methods: Twenty-eight patients with refractory MHC who underwent CSM-TACE were selected prospectively, and 5mL of peripheral blood was collected before surgery and on the 2nd and 5th day after surgery. Flow cytometry was used to detect immunological indicators. The early changes in levels of peripheral blood cell inflammatory factors Th1 (interleukin 2 (IL-2), tumor necrosis factor-α (TNF-a), interferon (IFN-r)), Th2 (IL-4, IL-6, IL-10), and Th17 (IL-17A) were observed after surgery, as well as the ratio of CD4+/CD8+. Results: All the 28 patients underwent CSM-TACE successfully. CT at 4 days after surgery showed clear outline low-density changes in liver tumors, and honeycomb necrosis was observed in the tumors in some cases. After CSM-TACE, the IL-6 and IL-10 levels were increased and then decreased again. After CSM-TACE, IL-2 showed a trend of transient increase and then decreased again, and the TNF-a level decreased temporarily, and then decreased. After surgery, the IFN-r level showed a continuous and slowly increasing trend. The IL-17 level showed a continuous downward trend, and the CD4+/CD8+ ratio showed a gradual and continuous upward trend, and there was a negative correlation between them. Conclusions: There are complex dynamic changes in TH1/Th2 in the early stage of CSM-TACE surgery, and the acute inflammatory response and the enhancement of the body's immune anti-tumor response coexist.